The Brazilian approach to internet intermediary liability: blueprint for a global regime? - Nicolo Zingales (Internet Policy Review, 2015)
While intermediary liability is becoming an of increasing importance in internet governance discussions, little is being made at the institutional level to minimise conflicts across jurisdictions and ensure the compliance of intermediary liability laws with fundamental rights and the freedom to innovate. The experience leading to the adoption of the Brazilian "Marco Civil da Internet" offers concrete insights for the definition of a baseline framework at the international level. This article also suggests the creation of a global forum of discussion on intermediary liability, allowing the interests of a variety of stakeholders to be taken into account in the definition and implementation of those baseline principles.
Keywords: 300; Intermediary liability; Internet governance; Marco Civil da Internet